Dissecting social decision-making: A spotlight on oxytocinergic transmission - Coccia, Giulia; La Greca, Filippo; Di Luca, Monica; Scheggia, Diego (Frontiers in Molecular Neuroscience, 2022)
Social decision-making requires the ability to balance self- and other-related interests to survive in social environments. Empathy is essential in regulating this type of interaction, often sustaining relevant prosocial behaviours such as altruism and helping behaviour. In the past decade, our capacity to assess affective and empathy-like behaviours in rodents expanded our understanding of the neurobiological substrates underlying social decision-making processes, such as prosocial behaviours. In this context, oxytocinergic transmission is profoundly implicated in modulating some of the major components of the social decision-making. Thus, this review will present the evidence on the association between oxytocin, empathy-like and prosocial behaviours in nonhuman animals. Then, we will dissect the involvement of oxytocinergic transmission, across different brain regions and pathways, in some of the key elements of social decision-making such as emotional discrimination, social recognition, emotional contagion, social dominance and social memory. As the evidence on the modulatory role of oxytocin on social decision-making raised considerable interest on its clinical relevance, we will also discuss the controversial findings on intranasal oxytocin- administration.